A strategy to increase lamb meat consumption from a relationship marketing perspective - María Teresa Maza; Keyla Alvarez; Pilar Uldemolins (Economía Agraria y Recursos Naturales)
A group of restaurants created a club around a lamb meat product to improve its promotion and achieve customers’ commitment and satisfaction. The objective is to analyse the relationship between the restaurateurs and the final consumer (B2C). A structured questionnaire survey was used to collect the data. Consumers like promotional activities, but their participation is rather low depending on age. From the structural equation model, it was determined that customer satisfaction has a high influence on customer commitment to the establishment; however, promotion and recognition have a very low influence on customer satisfaction and commitment.